2021
DOI: 10.1039/d0qi01101k
|View full text |Cite
|
Sign up to set email alerts
|

Rotation of fullerene molecules in the crystal lattice of fullerene/porphyrin: C60 and Sc3N@C80

Abstract: The dynamics of molecules in solid-state is important to understand their physicochemical properties. The temperature-dependent dynamics of Sc3N@C80 and C60 in the crystal lattice containing nickel octaethylporphyrin (NiOEP) was studied...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
1
9
1
Order By: Relevance
“…Indeed, all Tb sites in the crystal are located above the centers of Ni–N bonds in NiOEP-facing sides of fullerene cages (Figure S11). Similar preferential orientation of endohedral metal ions toward N–Ni–N leading to a considerable degree of the crystallographic order was reported for NiOEP cocrystals with nitride clusterfullerenes M 3 N@C 80 . , …”
Section: Resultssupporting
confidence: 70%
“…Indeed, all Tb sites in the crystal are located above the centers of Ni–N bonds in NiOEP-facing sides of fullerene cages (Figure S11). Similar preferential orientation of endohedral metal ions toward N–Ni–N leading to a considerable degree of the crystallographic order was reported for NiOEP cocrystals with nitride clusterfullerenes M 3 N@C 80 . , …”
Section: Resultssupporting
confidence: 70%
“…In a vast majority of M 3 N@C 80 •NiOEP co-crystals, two metal atoms of the M 3 N cluster are located above the N-Ni-N bonds. 63,64,81,86,87 The recently reported Tb 2 @C 80 (CF 3 ) co-crystallized with NiOEP also shows such tendency. 88 This effect seems to have an electrostatic nature as endohedral metals tend to situate close to negatively charged nitrogens of the porphyrin, 87 and this alignment was observed in the absence of Ni, when LaSc 2 N@C 80 fullerene was co-crystallized with H 2 OEP.…”
Section: Single-crystal X-ray Diffractionmentioning
confidence: 93%
“…[56][57][58] Likewise, the preferable fullerene cage isomers can be changed depending on the size and shape of the endohedral cluster. 9,[59][60][61] The size of the cluster and the associated internal strain was also shown to influence NMR and vibrational spectroscopic properties, 7,13,62 dynamics of the M 3 N cluster inside the cage, 63,64 preferable cycloaddition sites, [65][66][67][68] and even electrochemical potentials of endohedral Ce(IV/III) 14,15 and Ti(IV/III) 69,70 redox couples. Earlier study demonstrated that the replacement of Sc by Lu in both DySc 2 N@C 80 and Dy 2 ScN@C 80 metallofullerenes resulted in the noticeable variation of their dynamic magnetic properties and Dy•••Dy coupling.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] EMF molecules oen have certain structural exibility associated with the motion of the endohedral species, whose dynamics is apparently decoupled from that of the fullerene cage. For instance, nitride clusterfullerenes M 3 N@C 80 (M ¼ Sc, Y, lanthanides) exhibit a quasi-free rotation of the M 3 N cluster inside the fullerene near room temperature as evidenced experimentally by NMR spectroscopy 8,9 and variable-temperature single-crystal X-ray diffraction studies, 10,11 or computationally by molecular dynamics simulations. [12][13][14][15] But such a dynamic situation does not mean that there is no interaction between the fullerene host and its guest.…”
Section: Introductionmentioning
confidence: 99%